Qualidade de vida no trabalho: análise do caso de trabalhadores de uma empresa do ramo de metalurgia de Ponta Grossa - PR - Rosa, Marco Antonio Salles (2006)
This study it has for objective to demonstrate the perception of the workers of an industry of the metallurgic sector in the city of Ponta Grossa - PR, in relation to the question of the quality of life and its influence in the work environment. The work was developed searching to analyze these factors through descriptive statistical survey, where if it searched to analyze the Quality of Life of the workers of the point of view of the evaluated ones. The used methodology how much to the objectives of the work it is characterized as quantitative and how much to the problem, of exploratory model. As procedure technician a case study was carried through, in which the population of workers of the sector of assembly of metallic structures of a company of the branch of metallurgy of Ponta Grossa - PR, where the instrument of analysis WHOQOL-100 was applied, of the World-Wide Organization of Health was selected. The present work is concluded, through the answers gotten with the application of the instrument of analysis in the selected case, evidencing that the searched workers have a perception concerning Quality of Life in the Work who point, according to scale of answers: frequency, capacity and evaluation, that these are satisfied with its condition of Quality of Life. However, problems with the work environment had been detected among others factors, which intervene on the quality of life of the individual, concluding itself that measured they are necessary to minimize these problems. He is well-known that the investment in the human capital beyond a requirement brings an enormous return in form of quality and productivity for the company.